Handmade birthday card for Glenn Seaborg (1984)
Birthday card for Glenn Seaborg (1912-1999) signed by his colleagues and staff at the Lawrence Hall of Science. The card is hand illustrated with a drawing of Seaborg with Swedish-American actress and singer, Ann-Margret Olsson (1941-). The drawing is a copy of a photograph taken of the two at the Great Swedish Heritage Award ceremony. A speech bubble emerges from Seaborg's mouth and reads "I may be married, I may be older, but I'M NOT DEAD YET!"
Keywords: Seaborg, Glenn T. (Glenn Theodore), 1912-1999; Nobel Prize winners; Birthdays; Lawrence Hall of Science